Optical and Electrochromic Properties of Sol-Gel Deposited Doped Tungsten Oxide Films - Nilgün Özer; Carl M Lampert; Michael D. Rubin (1996)
The goal of this study is to investigate the effects of doping of tungsten oxide on its electrochromic properties. The work is directed toward the development of neutral coloring tungsten oxide materials with properties superior to undoped tungsten oxide. Two basic types of sol-gel formulations were used for experimentation. Type 1 used a WOCl4 precursor. Type 2 used a proprietary (Donnelly) tungsten complex precursor. The Type 2 precursor was used only for comparison to Type 1. Doping experiments were performed using the Type 1 chemistry. The dopants studied were Co, Cr, Nb, Ti, V and Y. The range of dopant was 1-12 mole %. Improved electrochromic behavior was observed for tungsten oxide films doped with V and Ti. Analysis of the films included x-ray diffraction, ellipsometry, cyclic voltammetry and spectrophotometry. X-ray diffraction showed that all films heat treated at temperatures below 300°C were amorphous in structure. The refractive indices for undoped films were measured. We found the n, k values of the Type 1 films to be lower than the Type 2 films. The n and k values were n=1.79 and k=2.8x10-3, and n=2.08 and k=3.6x10-3 at 550 nm, for Type 1 and Type 2 films respectively. Both types of tungsten oxide films showed low absorption and high transparency in the visible range. As expected, we found that the film density, and hence the refractive index and extinction coefficient, depended on coating solution chemistry, hydration, and densification procedures. Undoped Type 1 films showed slightly higher lithium diffusion coefficients (DLi), compared to undoped Type 2 films, DLi=1.36x 10-9 cm2 s-1 and 1.31 x 10-9 cm2 s-1, respectively. We also noted that the properties of the films could be reproduced for any coating chemistry and densification scheme. The electrochemical and optical behavior were determined by using an in-situ cuvette cell with a 1M LiCl04 / propylene carbonate electrolyte. Cyclic voltammetric measurements showed that doped Type 1 films exhibited electrochemical reversibility beyond 1200 cycles without change in charge capacity. A slight lowering of charge capacity was noted for the undoped films after cycling. The charge capacity for the V doped film was 16.9 mC/cm2 compared to undoped film, 9.6 mC/cm2. Spectrophotometry showed that doped films tended to exhibit a higher absorbance in their colored state compared to undoped films. Considerable improvement in the lithium diffusivity was noted for all the doped films. The greatest change was a factor of 20x for vanadium doping. Doping appeared to increase the cyclic durability of all the tungsten films out to 1200 cycles. Color changes by doping were noted for several dopants. The doped films with the best overall properties were about 8% vanadium and titanium tungsten oxide. The optimum concentration lies in the range of 7 to 12 mol%. The electrochromic color was a neutral brownish-blue for vanadium and grayish-blue for titanium doped tungsten oxide.

Sol-Gel Deposited Electrochromic Films for Electrochromic Smart Window Glass - Nilgün Özer; Carl M Lampert; Michael D. Rubin (International Symposium on Glass Problems, International Commission on Glass, 1996)
Electrochrornic windows offer the ability to dynamically change the transmittance of a glazing. With the appropriate sensor and controls, this smart window can be used for energy regulation and glare control for a variety of glazing applications. The most promising are building and automotive applications. This work covers the use of sol-gel deposition processes to make active films for these windows. The sol-gel process offers a low-capital investment for the deposition of these active films. Sol-gel serves as an alternative to more expensive vacuum deposition processes. The sol-gel process utilizes solution coating followed by a hydrolysis and condensation. In this investigation we report on tungsten oxide and nickel oxide films made by the sol-gel process for electrochromic windows. The properties of the sol-gel films compare favorably to those of films made by other techniques. A typical laminated electrochromic window consists of two glass sheets coated with transparent conductors, which are coated with the active films. The two sheets are laminated together with an ionically conductive polymer. The range of visible transmission modulation of the tungsten oxide was 60% and for the nickel oxide was 20%. We used the device configuration of glass/SnO2:F/WO3/polymer/LizNiOxHy/SnO2:F to test the films. The nickel oxide layer had a low level of lithiation and possibly contained a small amount of water. Lithiated oxymethylene-linked poly(ethylene oxide) was used as the laminating polymer. Commercially available Sn02:F/glass (LOF-Tec glass) was used as the transparent conducting glass. We found reasonable device switching characteristics which could be used for devices.

Chromogenic Switchable Glazing: Towards the Development of the Smart Window - Carl M Lampert (Proceedings of Window Innovations Conference 95, 1995)
The science and technology of chromogenic materials for switchable glazings in building applications is discussed. These glazings can be used for dynamic control of solar and visible energy. Currently many researchers and engineers are involved with the development of products in this field. A summary of activities in Japan, Europe, Australia, USA and Canada is made. The activities of the International Energy Agency are included. Both non-electrically activated and electrically activated glazings are discussed. Technologies covered in the first category are photochromics, and thermochromics and thermotropics. A discussion of electrically activated chromogenic glazings includes dispersed liquid crystals, dispersed particles and electrochromics. A selection of device structures and performance characteristics are compared. A discussion of transparent conductors is presented. Technical issues concerning large-area development of smart windows are discussed.

Electrochemical Lithium Insertion in Sol-gel Deposited LiNbO3 Films - Nilgün Özer; Carl M Lampert (Solar Energy Materials and Solar Cells, 1995)
Inorganic LiNbO3 ion conducting films were prepared by sol-gel process involving two alkoxides, lithium ethoxide and niobium ethoxide. The films were analyzed by ellipsometry, X-ray diffractometry, scanning electron microscopy and impedance spectroscopy. Impedance spectroscopy indicated that the Li+ conductivity values were in the range of 6-8 x 10-7 S cm-1. The morphology and thickness of these films played an important role in the insertion of lithium ions. Spectrophotometric investigation showed that LiNbO3 films exhibit very weak cathodic coloration from 350 to 900 nm spectral region. The previous termelectrochemical and opticalnext term properties clearly indicate that sol-gel deposited LiNbO3 films can be used as lithium ion conducting layers for electrochromic device application.

Optical and Electrochemical Characteristics of Niobium Oxide Films Prepared by Sol-Gel Process and Magnetron Sputtering: A Comparison - Nilgün Özer; Carl M Lampert; Michael D. Rubin (Solar Energy Materials and Solar Cells, 1995)
Electrochromic niobia (Nb205) coatings were prepared by the sot-gel spin-coating and d.c. magnetron sputtering techniques. Parameters were investigated for the process fabrication of sol-gel spin coated Nb205 films exhibiting high coloration efficiency comparable with that d.c. magnetron sputtered niobia films. X-ray diffraction studies (XRD) showed that the sot-gel deposited and magnetron sputtered films heat treated at temperatures below 450°C, were amorphous, whereas those heat treated at higher temperatures were slightly crystalline. X-ray photoelectron spectroscopy (XPS) studies showed that the stoichiometry of the films was Nb205. The refractive index and electrochromic coloration were found to depend on the preparation technique. Both films showed low absorption and high transparency in the visible range. We found that the n, k values of the sot-gel deposited films to be lower than for the sputtered films. The n and k values were n = 1.82 and k = 3 × 10−3, and n = 2.28 and k = 4 × 10−3 at 530 urn for sot-gel deposited and sputtered films, respectively. The electrochemical behavior and structural changes were investigated in 1 M LiC104/propylene carbonate solution. Using the electrochemical measurements and X-ray photoelectron spectroscopy, the probable electrode reaction with the lithiation and delithiation is Nb2O5 + x Li+ + x e− ↔ LixNb205. Cyclic voltametric (CV) measurements showed that both Nb205 films exhibits electrochemical reversibility beyond 1200 cycles without change in performance. “In situ” optical measurement revealed that those films exhibit an electrochromic effect in the spectral range 300 < λ < 2100 nm but remain unchanged in the infrared spectral range. The change in visible transmittance was 40% for 250 nm thick electrodes. Spectroelectrochemical measurements showed that spin coated films were essentially electrochemically equivalent to those prepared by d.c. magnetron sputter deposition.
Keywords: D.C. magnetron sputtering; electrochromism; Niobia; optical properties; sol-gel deposition

Optical and Electrochemical Properties of Sol-gel Spin Coated CeO2-TiO2 Films - Nilgün Özer; Selmar DeSouza; Carl M Lampert (SPIE Meeting, 1995)
The optical and electrochemical properties of sol-gel spin coated Ce02-TiO2 (50% CeO2) films were investigated for electrochrornic applications. The coating solutions were prepared by using mixed organic-inorganic | Ti(OC2H5)4 and Ce(NH4)2 (NO3)6 | precursors. X-ray diffraction studies showed the sol-gel spin-coated films were composed of an amorphous matrix of titanium oxide containing nanocrystallites of cerium oxide. The coating solar transmission value was Ts=0.8 (250 nm thick). The refractive index and the extinction coefficient were derived from transmittance measurements in the UV-VIS-NIR regions. These films had refractive index value of n=2.18 and extinction coefficient value of k=8x10-4 at λ=550 nm. Cyclic voltametric measurements showed reversible electrochemical insertion of lithium ions in a CeO2-TiO2/LiClO4-propylene carbonate electrochemical cell. During cycling the films maintain high optical transmittance. Spectrophotometric and electrochemical investigations performed on CeO2-TiO2 films revealed that these films are suitable as an optically passive counter-electrode in lithium electrochromic devices.
Keywords: cerium oxide-titanium oxide; counter electrode; electrochemical properties; electrochromic device; optical properties; sol-gel deposition

Preparation and Properties of Spin-Coated Nb2O5 Films by the Sol-Gel Process for Electrochemical Applications - Nilgün Özer; Din-Guo Chen; Carl M Lampert (Thin Solid Films, 1995)
The preparation and properties of Nb2O5 coatings made by the sol-gel process were investigated. The films were deposited by spin coating on In2O3:Sn/glass and quartz substrates from a polymeric solutions of niobia derived from niobium ethoxide. The films were characterized by investigation of the stoichiometry, refractive index, optical transmission, electrochemical behavior, and the microstructure. X-ray diffraction studies showed the films to be amorphous for heat treatments below 450 °C. X-ray photoelectron spectroscopy (XPS) measurement revealed the O:Nb atomic stoichiometry to be 5:2. Cyclic voltammetric measurements showed that the Nb2O5/1 M LiClO4-propylene carbonate system exhibits electrochemical reversibility beyond 1200 cycles without change in performance. In situ UV-Vis-NIR spectroelectrochemical measurement revealed that Nb2O5 films exhibit an electrochromic effect in the spectral range 300<λ<2100 nm and remain unchanged in the infrared spectral range. The change in visible transmittance was 40% for a 250 nm thick electrode. XPS spectra indicate that Nb(V) is reduced to a lower valence state Nb(IV) in a colored state with injected Li+. The bronze coloration is due to a simultaneous injection of electrons and Li+ ions into Nb2O5. The sol-gel-deposited Nb2O5 films are useful for cathodically coloring electrochromic electrodes in electrochromic devices.
Keywords: Electrochemistry; Niobium oxide; optical properties; X-ray photoelectron spectroscopy

Sol-Gel Deposited Amorphous Tantalum Oxide and Niobium Oxide Films as Protonic Conductors - Nilgün Özer; Carl M Lampert (Window Innovations 95 Conference Proceedings, 1995)
In this work we report on the preparation of tantalum oxide and niobium oxide films by the sol-gel method for use as proton ion conductors in electrochromic devices. Measurement of the proton conductivity was derived from impedence spectroscopy measurements. The proton conductivity for Ta2O5 and NbO5 films was 4.6 x 10-6 Scm-1 and 3.2 x 10-7 Scm-1 respectively. The structural and chemical properties of the films were investigated by X-ray diffraction, X-ray photoelectron spectroscopy and scanning electron microscopy. These films were found to be amorphous and close to the stoichometry of Ta2O5 and NbO5 respectively. In order to estimate the compatibility of these sol-gel deposited layers as ion conductors for EC devices, we investigated tantalum oxide and niobium oxide films deposited on sputtered WO3 films. Charge balance and coloration characteristics were investigated during voltammetric cycling in a pH 2 liquid electrolyte. Spectral transmittance was measured for colored and bleached conditions. The photopic weighted transmittance change and solar weighted transmittance change were Tp=35.2% - 21.8% and Ts=75.7% - 14.2% for tantala films on tungsten oxide. For niobia on tungsten oxide the values were Tp=85.3% - 35.2% and Ts=75.8% - 28.1%.

Sol-Gel Deposited Electrochromic Coatings - Nilgün Özer; Carl M Lampert (Am. Optical Society, Technical Digest, 1995)
Electrochromic devices have increasing application in display devices, switchable minors and smart windows. A variety of vacuum depition technologies have been used to make electrochromic devices. The sol-gel process offers an alternative approach to the synthesis of optical quality and low cost electrochromic device layers. This study summarizes the developments in sol-gel deposited electrochromic films. The sol-gel process involves the formation of oxide networks upon hydrolysis-condensation of alkoxide precursors. In this study we cover the sol-gel deposited oxides of WO3, V2O5, TiO2, Nb2O5 and NiOx.

Structural and Optical Properties of Sol-Gel Deposited Proton Conducting Ta2O5 Films - Nilgün Özer; Carl M Lampert (8th International Workshop on Glasses and Ceramics From Gels, 1995)
Proton conducting tantalum oxide films were deposited by spin coating using a sol-gel process. The coating solutions were prepared using Ta(OC2H5)5 as a precursor. X-ray diffraction studies determined that the sol-gel films, heat treated at temperatures below 400 °C, were amorphous. Films heat treated at higher temperatures were crystalline Ta2O5. The solar transmission values (Ts) of tantala films on glass generally range from 0.8-0.9 depending on thickness. The refractive index and the extinction coefficient were evaluated from transmittance characteristics in the UV-VIS-NIR regions. The refractive index values calculated at λ=550 nm increased from n=1.78 to 1.97 with increasing heat treatment from 150 to 450 °C. The films heat treated at different temperatures showed low absorption with extinction coefficients of less than k=1 x 10-3 in the visible range. Spectrophotometric and impedance spectroscopic investigations performed on Ta2O5 films revealed that these films have protonic conductivity of 3.2 x 10-6 S/cm. The films are suitable for proton conducting layers in electrochromic (EC) devices.
Keywords: electrochromic devices; optical proterties; proton conductor; tantalum oxide

Switchable Glazing: Science and Technology of Smart Windows - Carl M Lampert (Society of Vacuum Coaters 38th Annual Technical Conference, 1995)
Electrically activated switchable glazing and their use as smart windows and other large-area applications are discussed. Electrochromic devices are compared to dispersed liquid crystals and dispersed particle glazing systems. A selection of device structures and performance characteristics are compared. A discussion of transparent conductors is presented. The characteristics of prototype and commercial devices from commercial and university labs in Japan, Europe, Australia, and USA are covered. A discussion of the future of this technology is made including areas of necessary development for the realization of devices in excess of 1 m2.

Characterization of Sol-Gel Deposited Niobium Pentoxide Films for Electrochromic Devices - Nilgün Özer; Timothy Barreto; Temel Buyuklimanl; Carl M Lampert (Solar Energy Materials and Solar Cells, 1994)
Niobium pentoxide films, fabricated by the sol-gel process, were spin coated onto conductive indium tin oxide (ITO)/glass, and microscope slides. These films were cycled in a 1M LiClO4 propylene carbonate (PC) solution, and exhibited electrochromic behavior upon the electrochemical insertion (reduction) and extraction (oxidation) of lithium. In-situ optical transmittance measurements were investigated in the ultraviolet/visible/near-infrared wavelength regions (250-2100 nm). Niobium pentoxide films showed reversible optical switching from 320 to 870 nm, but were found electrochromically inactive in the infrared region. Surface analysis using X-ray photoelectron spectroscopy (XPS) indicated little difference in the chemistry of Nb2O5 films as deposited and lithiated LixNb2O5 films, as XPS binding energies of Nb and O showed no appreciable shifts. These films were found to be amorphous by X-ray diffraction. Optical transmittance measurements combined with cyclic voltamograms and XPS spectra, revealed that the electrochromic behavior of these films occurs due to the insertion of Li+ cations into niobium pentoxide films. The bronze coloration of the niobium pentoxide films could make them useful as an electrochromic counter electrodesfor electrochromic devices.

Characterization of Tantalum Oxide Films Prepared by Sol-Gel Process for electrochemical devices - Nilgün Özer; Yongxiang He; Carl M Lampert (1994)
Tantalum oxide films were prepared by sol-gel process using tantalum ethoxide Ta(OC2H5)5. The dependence of deposition conditions (i.e. composition of polymeric solutions and spinning rate) on ionic conductivities for tantalum oxide films were studied. The best results achieved for films fabricated by the spin coating technique were from clear polymeric solutions. These films had low packing density ρ=3.2 g/cm3 and good proton conductivity (about 10-6 Ω-1 cm-1). X-ray photoelectron spectroscopy (XPS) was used for studying the compositions of the tantalum oxide films. We report on the use of tantalum oxide films as ion conductors in devices consisting of WO3/Ta2O5/H+ ion storage polymer structure. We found tantalum oxide to have very good properties for proton device applications.

Glazing Material for Solar and Architectural Applications - Windows and Daylighting Group (1994)
This report summarizes five collaborative research projects on glazings performed by participants in Subtask C of IEA Solar Heating and Cooling Programme (SHC) Task 10, Materials Research and Testing. The projects include materials characterization, optical and thermal measurements, and durability testing of several types of new glazings. Three studies were completed on electrochromic and dispersed liquid crystals for smart windows, and two were completed for low-E coatings and transparent insulation materials for more conventional window and wall applications. In the area of optical switching materials for smart windows, the group developed more uniform characterization parameters that are useful to determine lifetime and performance of electrochromics. The detailed optical properties of an Asahi (Japan) prototype electrochromic window were measured in several laboratories. A one square meter array of prototype devices was tested outdoors and demonstrated significant cooling savings compared to tinted static glazing. Three dispersed liquid crystal window devices from Taliq (USA) were evaluated. In the off state, these liquid crystal windows scatter light greatly. When a voltage of about 100 V ac is applied, these windows become transparent. Undyed devices reduce total visible light transmittance by only .25 when switched, but this can be increased to .50 with the use of dyed liquid crystals. A wide range of solar-optical and emittance measurements were made on low-E coated glass and plastic. Samples of pyrolytic tin oxide from Ford glass (USA) and multilayer metal-dielectric coatings from Interpane (Germany) and Southwall (USA) were evaluated. In addition to optical characterization, the samples were exposure-tested in Switzerland. The thermal and optical properties of two different types of transparent insulation materials were measured. Samples of the polycarbonate honeycomb (supplied by Arel in Israel) and monolithic aerogel (supplied by Airglass in Sweden) were evaluated. Discrepancies in the round robin thermal measurements for the honeycomb material pointed out some measurement problems due to different equipment and procedures used. Overall, these glazing studies were successful in improving the understanding and use of advanced glazings. Follow-on work on most of these glazings will be continued in the new IEA SHC Task 18, Advanced Glazing Materials.

Characteristics of Laminated Electrochromic Devices Using Polyorganodisulfate Electrodes - Carl M Lampert; Steven J. Visco; Marca M. Doeff; Yan Ping Ma; Yongxiang He; Jean-Christophe Giron (SPIE Proceedings 2017, 1993)
The use of polyorganodisulfides as optically passive counterelectrodes in a variety of electrochromic devices are discussed. Characteristic data is presented for electrochmmic devices using proton, and lithium coloration ions with polyethylene oxide electrolyte and polydimercaptothiadiazole positive electrodes. Solid state devices consisting of molybdenum doped W03, amorphous polyethylene oxide electrolyte (a-PEO), and a polyorganodisulfide counter-electrode colored rapidly from a pale yellow to a deep blue-green, upon application of 1.2 V d.c. The photopic transmittance changed from 61 to 98, and the solar transmittance from 45 to 5% during the coloration process. Also, our experiments with polyimidazole are detailed. This family of compounds due to its unique electrical and ion conduction properties allow a single composite ion storage and ion conductor electrode to be made, simplifying the device construction. Devices rnade from this family of compounds color to deep blue-gray upon application of 1.2-1.5 V. Bleaching occurs at -0.4 to -0.5 s. The photopic transmittance changed from 55 to 9%. and the solar transmittance from 34 to 4% during coloration. Both coloration and bleaching are quite rapid.

Optical Switching Technology for Glazing - Carl M Lampert (Thin Solid Films, 1993)
The technology of optical switching devices for dynamic glazings and other applications is discussed. The status of the state of the industry and its developments is detailed. The technical emphasis will be on the properties of chromogenic materials covering electrochromic, phase-dispersed liquid crystals and dispersed-particle systems. Such technologies can be used for dynamic control of solar energy through building and vehicle glazings. Both visible and solar control can be obtained from these devices. Switching ranges can be from as high as 80% to 5-10% transmittance in the visible region. The energy and daylighting benefits of such glazings are discussed. Also, chromogenic glazings can be used for other product applications such as the modulation of reflector surfaces and large electronic information display systems. The science of selected electrochromic devices is covered. Technical issues concerning large-scale chromogenic devices are discussed.

Towards Large-area Photovoltaic Nanocells: Experiences Learned from Smart Window Technology - Carl M Lampert (Solar Energy Materials and Solar Cells, 1993)
This investigation covers two technologies which have different applications but have many similar characteristics. One is the nanocell photoelectrochemical solar cell, the other is the electrochromic window. At first it is hard to see what they have in common other then that they both interact with light.